2003
DOI: 10.1128/jcm.41.10.4767-4778.2003
|View full text |Cite
|
Sign up to set email alerts
|

Species Diversity and Polymorphism in theExophiala spiniferaClade Containing Opportunistic Black Yeast-Like Fungi

Abstract: A monophyletic group of black yeast-like fungi containing opportunistic pathogens around Exophiala spinifera is analyzed using sequences of the small-subunit (SSU) and internal transcribed spacer (ITS) domains of ribosomal DNA. The group contains yeast-like and annellidic species (anamorph genus Exophiala) in addition to sympodial taxa (anamorph genera Ramichloridium and Rhinocladiella). The new species Exophiala oligosperma, Ramichloridium basitonum, and Rhinocladiella similis are introduced and compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
145
0
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(156 citation statements)
references
References 29 publications
6
145
0
5
Order By: Relevance
“…However, they can be distinguished by conidial morphology and size, i.e. subglobose to ellipsoidal and 2.5-3.8 × 1.8-2.5 μm in R. anceps, short-cylindrical and 3.7-5.5 × 1.2-1.8 μm in R. atrovirens, guttuliform to clavate and 3.5-4.5 × 2.2 μm in R. basitona, and cylindrical, 4-7 × 1.5 μm in R. similis (de Hoog and Hermanides-Nijhof 1977;de Hoog et al 2003). Furthermore, the yeast cells that are often produced in culture by R. anceps, R. atrovirens and R. similis (de Hoog and Hermanides-Nijhof 1977;de Hoog et al 2000de Hoog et al , 2003 were not observed in R. amoena.…”
Section: Cyphellophora Chlamydosporamentioning
confidence: 99%
“…However, they can be distinguished by conidial morphology and size, i.e. subglobose to ellipsoidal and 2.5-3.8 × 1.8-2.5 μm in R. anceps, short-cylindrical and 3.7-5.5 × 1.2-1.8 μm in R. atrovirens, guttuliform to clavate and 3.5-4.5 × 2.2 μm in R. basitona, and cylindrical, 4-7 × 1.5 μm in R. similis (de Hoog and Hermanides-Nijhof 1977;de Hoog et al 2003). Furthermore, the yeast cells that are often produced in culture by R. anceps, R. atrovirens and R. similis (de Hoog and Hermanides-Nijhof 1977;de Hoog et al 2000de Hoog et al , 2003 were not observed in R. amoena.…”
Section: Cyphellophora Chlamydosporamentioning
confidence: 99%
“…The family Herpotrichiellaceae of the class Eurotiomycetes of Ascomycota was present at high levels only in the Dongdo sample, whereas the family Trichocomaceae comprised greater than 1.0% of all families detected in the Dongdo and Seodo samples. Members of Herpotrichiellaceae have been characterized as human pathogens (de Hoog et al, 2003;Haase et al, 1999), while members of Trichocomaceae maintain saprophytic, pathogenic, and/or endophytic characteristics (da Costa et al, 1998;Khan et al, 2008;Samson et al, 2004;Valdez et al, 2006). The families Clavicipitaceae and Hypocreaceae of the class Sordariomycetes of Ascomycota were slightly more abundant in the Dongdo sample than in the Ulleungdo Fungal classes with a relative abundance greater than 1% in at least one of the three samples are shown.…”
Section: Archaeorhizomycetesmentioning
confidence: 99%
“…The Dictionary of Fungi (Kirk et al, 2001) cites twelve species in the genus Exophiala; however, additional species have been described more recently (e.g. de Hoog et al, 2003). Some species of the genus Exophiala are known as occasional opportunistic human pathogens (de Hoog et al, 2003;Haase et al, 1999).…”
mentioning
confidence: 99%
“…However, the use of nuclear ribosomal RNA (nrRNA) gene sequence data has facilitated identification and classification of these organisms (see Spatafora et al, 1995;Untereiner & Naveau, 1999;de Hoog et al, 2003). The family is represented by the teleomorph genus Capronia and the anamorphic genera Cladophialophora, Exophiala, Fonsecaea, Phaeococcomyces, Phialophora, Ramichloridium and Rhinocladiella (Untereiner & Naveau, 1999).…”
mentioning
confidence: 99%
See 1 more Smart Citation